Psychological Support as an Effective form of Professional Self-determination - Papoyan, Varduհi; Muradyan, Yelena; Galstyan, Alina (Bulletin of Yerevan University E: Philosophy, Psychology, 2016)
The problem of psychological support of professional self-determination of senior schoolchildren is considered in this article. Spatial attention is paid to the career guidance at school, in particular, in such form as professional counseling. Results of experiments have revealed difficulties in the professional self-determination of senior schoolchildren.
Keywords: professional self-determination, vocation guidance work, vocational counseling, psychological support, choice of profession